Does Oil Prices Uncertainty Affect Stock Returns in Russia: A Bivariate GARCH-in-Mean Approach - Bass, Alexander (International Journal of Energy Economics and Policy, 2017)
In this article, we explore the dependence of the volatility of stock returns and the world oil prices on the example of Russia. Using weekly data for the variables for the period from 01.01.2003 by 01.05.2017, we define the uncertainty of oil prices as the conditional standard deviation of the one-step-ahead forecast error for changes in oil prices. A bivariate GARCH-in-mean vector autoregressive model is used for the study. The results of the study show that, given oil prices are denominated in U.S. dollars, the uncertainty of oil prices has a positive and statistically significant impact on stock returns. Also as a result of research, we come to the conclusion that in case of Russia, the uncertainty of oil prices in the equation "oil price-stock returns" leads to an increased positive response of stock returns to a positive oil price shock, while increasing the sensitivity of stock returns to negative oil price shock in comparison with the model, not taking into account the uncertainty of oil prices. The analysis also showed that the response of stock returns to positive and negative oil price shocks uncertainty is asymmetric. Keywords: oil prices, stock returns, volatility, GARCH, emerging market. JEL Classifications: C32, G10, G15, Q43